Industrial revolution in literary imagination responses from three phases: the romantic, the victorian and the late victorian period - Sultana, Afreen (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.